2014
DOI: 10.1155/2014/218293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nigella sativa (Habbatus sauda) Oil and Nicotine Chronic Treatments on Sperm Parameters and Testis Histological Features of Rats

Abstract: Twenty-four Sprague-Dawley male rats (7–9 weeks old, 200–250 g) were divided into Nicotine (N) (0.5 mg/100 g body weight (BW), Nicotine Control (NC) (saline, 0.1 mL/100 g BW), Habbatus sauda oil (HS) (6.0 μL/100 g BW), and Habbatus sauda Control (HSC) (corn oil, 0.1 mL/100 g BW) groups and treated for 100 days. Sperm parameters and seminiferous tubules measurements were evaluated. The N showed a significantly lower sperm motility (1.03 ± 0.05 × 106 sperm/mL) and percentage of normal (82.61 ± 0.03%) and live (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
(37 reference statements)
1
10
0
2
Order By: Relevance
“…Cells appeared disorganized and dissociated from each other and exhibited pyknotic nuclei and densely stained cytoplasm. These findings are in agreement with a previous study which reported that male Wistar rats treated with varied doses of nicotine for 30 days also showed a reduction in germ cells and spermatids of their seminiferous tubules [17]. On the other hand, some temporary effects on testes histopathology of rats aged 7 weeks when exposed to nicotine were also reported [24].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Cells appeared disorganized and dissociated from each other and exhibited pyknotic nuclei and densely stained cytoplasm. These findings are in agreement with a previous study which reported that male Wistar rats treated with varied doses of nicotine for 30 days also showed a reduction in germ cells and spermatids of their seminiferous tubules [17]. On the other hand, some temporary effects on testes histopathology of rats aged 7 weeks when exposed to nicotine were also reported [24].…”
Section: Discussionsupporting
confidence: 93%
“…Rats were chosen as the experimental animal in this research for their well-defined reproductive systems and the fact that compounds which could cause infertility in human males were also found to be active in rats [17]. Five to six developmental time periods, indicated in post natal days (PNDs), are recognized in the male rat and were referenced when characterizing microscopic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TQ has demonstrated some protective roles in relation to oxidative status, such as superoxide anion scavenger, direct cytoprotective effects and indirect antioxidant and androgen activities (Hala, ). Moreover, TQ can affect oxidative phosphorylation enzymes and protect cells against free radicals (Cho Ping, Hashim, & Hasan‐Adli, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite reports of its antifertility and antiandrogenic capacities in male rabbits, rats and mice (Kamal et al 1993;Kassem et al 2006;Al-Janabi 2011), fenugreek exerted reversal of lindane-associated reactive oxygen species (ROS)-damage in male rat's reproductive and accessory organs with restoration of fertility, testosterone levels and amelioration of functionality (Seshadri et al 2011). On the other hand, N. sativa oil is promoted as a male fertility agent (Ghazeeri et al 2012) and could ameliorate and reverse the nicotine-induced reduction in sperm motility and morphology and affected testicular histology (Cho Ping et al 2014). It was also found to improve hyperlipidemic male rat fertility and spermatogenesis (Bashandy 2007;Al-Saaidi et al 2009;Mohammad et al 2009;Parandin et al 2012;Mansour et al 2013;Marbat et al 2013).…”
Section: Herbal Remedies Of Male Fertility/infertility Issuesmentioning
confidence: 99%